Complete Basic Immunization for Babies at the Manisa Health Center - Hanifah, Astin Nur; Achmad, Viyan Septiyana; Reffita, Lea Ingne; Rosida, Rosida; Rihi, Pryati; Ratulangi, Jeane Irene Levy; Nurhaedah, Nurhaedah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Immunization is the most effective and efficient public health effort in preventing diseases and reducing mortality, such as smallpox, polio, tuberculosis, hepatitis B, diphtheria, measles, rubella and congenital rubella syndrome (CRS), tetanus, pneumonia (inflammation of lungs) and meningitis (inflammation of the lining of the brain). Immunization aims to provide immunity to the child's body by administering a vaccine. Vaccine is a drug that is given to help prevent a disease. There are still many who have not received complete immunization due to various reasons such as lack of knowledge of mothers about immunization and low awareness of mothers bringing their babies to Posyandu or Puskesmas to get complete immunization, lack of explanation from health workers about the benefits of immunization including the factor of low maternal education. The purpose of this study was to determine the relationship between education, knowledge and attitudes of mothers at the Manisa Health Center. This research is analytic with a cross sectional approach, in this study were mothers who had babies, with a total sampling technique obtained 30 respondents. Data collection was carried out using a questionnaire as a research instrument. The data that has been collected is then processed and analyzed using the chi-square test. The results of statistical analysis, obtained a relationship between education and completeness of basic immunization in infants (0.007 <0.05), there is a relationship between knowledge and completeness of basic immunization in infants (0.000 <0.05) and there is a relationship between attitude and completeness of basic immunization in infants (0.000 <0.05). Based on the results of this study it was concluded that there was a relationship between education, knowledge and attitudes of mothers with the completeness of basic immunization in infants. Through this research, it is hoped that health workers at the Manisa Health Center will be more active in providing counseling and information about immunization services and for researchers to add experience and apply the knowledge they have gained.